Leitura e biblioteca escolar: uma proposta de levar a ler em “lugares distantes” - MESQUITA, Alessandra Maria de (Universidade Federal do Oeste do Pará, 2021)
This work has as its theme: Reading and school library: a proposal to take reading in "distant places". It is linked to the Professional Master's Program in Literature - Profile, the Study Group Reading and Intervention in Children and Youth Literature in school - Lelit, Federal University of West of Pará - Ufopa - and follows the research line Children's Literature, litera-ture and education, reader training. The purpose of this study is to investigate the conditions and possibilities of establishing a place to read at the RosáliaSimões Barbosa Municipal School of Elementary Education in Monte Alegre-PA. The adopted meth-odology consists of intervention research with the organization of a library in the school and the development of reading activities. The study began in the first semester of 2017 and lasted until 2018, but I intend to continue to observe whether the school will give continuity to the actions of reading. The theoretical basis is: Britto (2012, 2015), Candido (2011), Silva (1984, 1993), Santos (2016), Bértolo (2014) and Saviani and Duarte (2010). The results indicate that there was an enthusiasm of the school to use the organized school library and to carry out ac-tivities of reading with the students. However, it did not reach a more solid proposal of the entire faculty. Some actions were continuous, but not collective.